NUTRITION STATUS SCREENING AND BALANCED NUTRITION EDUCATION IN ELDERLY AT MALANG REGENCY - Ni Njoman Juliasih; Minarni Wartiningsih; Hanna Tabita Hasianna Silitonga; Eric Dino Tandoyo; Nathania Disa Ariesta Andriani; Abigail Elsha Tiara Susanto; Rifka Irhamna; Donny Arintha Putra Gabriella; Muhammad Amin Rais; Adellita Ilmas Bintang Mohamad (JURNAL PENGABDIAN MANDIRI, 2022)
There is a decrease in the physiological function of the body in the elderly which causes the elderly to be more susceptible to health and nutrition problems. The nutritional problem that needs to be watched out in the elderly group is obesity. Elderly with obesity are at greater risk of experiencing degenerative diseases compared to the elderly who have normal nutritional status. This activity is divided into three stages in its implementation. First stage is a preliminary study by conducting nutritional screening to determine the nutritional problems. The second stage is data analysis and preparation of educational materials according to the results of the preliminary study. The last stage is performing nutrition education to the elderly. The results of the preliminary study that have been carried out show that the majority of the elderly in RT 04 RW 01 Kertorejo Hamlet Peniwen Village, Kromengan District, Malang Regency have more nutritional status with a high calorie consumption pattern. Based on these results, educational activities related to balanced nutrition were carried out with the result of increasing knowledge of the elderly who were accompanied by the family.